A modified transactional model of stress and coping on depressive symptoms among informal caregivers of persons with dementia - Yuan, Qi; Tan, Tee Hng; Wang, Peizhi; Poremski, Daniel; Abdin, Edimansyah; Magadi, Harish; Goveas, Richard; Ng, Li Ling; Subramaniam, Mythily (Scientific reports, 2024)
Informal caregivers are crucial to the care of persons with dementia (PWD), but their role is often reported as challenging. This study aims to examine caregiver stress and depressive symptoms among informal caregivers of PWD using a modified transactional stress and coping model. Path analysis was conducted among a sample of informal caregivers of PWD in Singapore ( n = 281) using information on functional dependence and memory and behavioral problems of PWD, and self-reported measurements on caregivers’ knowledge of dementia, perceived positive aspects of caregiving, social support, coping patterns, caregiving self-efficacy, caregiving burden and depressive symptoms. The initial model reflecting our assumptions for the transactional stress and coping model showed a poor fit (model 1 - CFI = 0.858, TLI = 0.665, RMSEA = 0.118). Logical modifications were made until sufficient model fit was achieved (model 2 - CFI = 0.987, TLI = 0.955, RMSEA = 0.043). We then removed the insignificant paths in model 2 and obtained our final model (model 3 - CFI = 0.990, TLI = 0.974, RMSEA = 0.033). The final model supported our hypotheses, with some adjustments. This study advances our understanding of caregiver distress by modifying the transactional stress and coping model, including (1) the key role of caregiver self-efficacy in the primary appraisal process, (2) the dynamic assessment of coping resources across all stages of the model, and (3) the importance of coping patterns. Future studies could explore the generalizability of these findings.